Scaffold-free 3D-cell co-culture model system for the study of metastatic cancer in the brain TME - Pratistha Sarkar; Shreya Ahuja; Iulia M. Lazar (PLoS ONE, 2026)
Cancer involves complex and dynamic interactions among tumor, stromal, immune cells, and the surrounding matrix, however, the protected microenvironment of the brain limits direct access and the execution of mechanistic studies. In this work, we developed a scaffold-free in-vitro brain endothelial–cancer interaction model based on a newly identified affinity between endothelial and cancer cells that enables them to self-assemble into 3D networked constructs supported by high endothelial collagen production and chemokine secretion from both cell types. The model was constructed from human brain endothelial cells (HBEC-5i) and three cancer cell lines derived from breast (MDA-MB-231/triple negative and SK-BR-3/HER2+) and aggressive ovarian (SK-OV-3) cancers. We show that the model mimics the attachment of metastasized cancer cells to the brain networked microvasculature, enabling the study of temporal changes in endothelial morphology and molecular signaling processes that sustain cancer cell migration, survival, proliferation, and angiogenic processes. Moreover, the model exhibits long-term stability, reproducibility, and potential for evaluating anti-cancer agents. Altogether, this simple scaffold-free 3D model offers a low-cost, physiologically relevant tool for studying cancer-endothelial crosstalk and key biological processes that unfold in the tumor microenvironment, to ultimately improve diagnostic capabilities and patient outcomes.